Analisisis Faktor Penyebab Gangguan Perkembangan Pada Siswa Madrasah Ibtidaiyyah dan Implikasinya Terhadap Pembelajaran - Miftakhunnisa Damayanti; Indah Lestari; Mochamad Widjanarko (PGSD Universitas Muria Kudus, 2026)
This study aims to analyze the factors causing developmental disorders among first-grade students at Madrasah Ibtidaiyyah (MI) Al-Fattah and to examine their implications for the learning process. This research employed a qualitative descriptive approach to obtain an in- depth understanding of students’ developmental conditions in a natural classroom setting. The subjects of the study were 11 first-grade students of MI Al-Fattah, while the informants included the class teacher and the school principal. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that students experienced various developmental disorders across several aspects, including attention and concentration, language and communication, social interaction, and basic literacy skills. Difficulties in basic literacy and attention were identified as the most dominant issues affecting students’ readiness to learn and participation in classroom activities. These developmental challenges were influenced by a combination of internal factors, such as students’ cognitive readiness and self-confidence, and external factors, including learning strategies and classroom environments that were not yet fully adaptive. The study concludes that developmental disorders among early-grade students are multidimensional and require adaptive, inclusive, and responsive learning strategies. The findings are expected to provide practical implications for teachers in designing differentiated learning approaches that accommodate students’ diverse developmental needs.